Transformations in Coastal Communities: A Case Study of Tourism Development at BTN Lungkak Beach, East Lombok - Susilawati; Emilia Agustina (Jurnal Pendidikan Sosial Indonesia, 2025)
Purpose - Coastal tourism has rapidly expanded in Indonesia, yet its impact on local community structures and cultural values remains underexplored. This study aims to understand how tourism at BTN Lungkak Beach has triggered socio-cultural transformation in Ketapang Raya Village. The study is significant due to the lack of context-specific research focusing on social change from the perspective of coastal communities. Design/Methods/Approach - A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, field observations, and documentation involving community leaders, tourism stakeholders, and local residents. Thematic analysis was used to identify emerging patterns of social and cultural change associated with tourism activities. Findings - The study found significant shifts in social structure, gender roles, communication patterns, and local value systems. The community showed ambivalence between adapting to modernity and preserving traditions. Furthermore, tourism created unequal economic participation across social groups. Research Implications/Limitations - The findings highlight the necessity of community-based tourism management that balances economic benefits with the preservation of local socio-cultural values. The study’s limitations include its geographically narrow scope and context-specific qualitative data, which may limit generalizability of the results.